Ontology-based HBIM for historic buildings with traditional woodwork in Taiwan - Cheng, Ying-Mei; Kuo, Chiao-Ling; Mou, Chia-Ching (Journal of Civil Engineering and Management, 2021)
In recent years, the use of Historic Building Information Modeling (HBIM) has grown prevalent and thus provided a research opportunity. Differing from newly constructed buildings, structural components of historic buildings come with unique physical configurations and have amassed impressive amount of restoration data, all of which must be taken into consideration when incorporating Building Information Modeling. In terms of modelling, it is critical to determine the appropriate level of detail (LoD), level of information (LoI), especially the comprehensiveness and expandability of the database. International Committee for Documentation/Conceptual Reference Model (CIDOC CRM) is a widely accepted standard for ontology model. This study aims to integrate the HBIM and CIDOC CRM to construct a framework and comprehensive operational procedure for the modeling of traditional Minan architecture and a database with complete semantics archiving the background and restoration data. Autodesk A360 is ideal for collaborative. However, there are limitations when it comes to developing advanced models for data management or query; interactive experience; meeting model applications derived from future scenarios. Therefore, the study also offers a 3D modeling platform constructed using Unity, as well as a comparison of the platforms built with Unity, three.js and Autodesk A360 as a reference for users.